Influence of selected exercise on serum immunoglobulin, testosterone and cortisol in semi-endurance elite runners - Hejazi, K.; Attarzadeh Hosseini, S. R. (Asian Journal of Sports Medicine, 2012)
Purpose: The aim of this study was to compare the levels of serum immunoglobulin (IgA, IgM, IgG), testosterone and cortisol in semi-endurance elite runners during general preparation and competition phase of training.